PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI DIGITAL PREZI UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PEMBELAJARAN IPS KELAS V - Rosalinda; Ira Restu Kurnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The development of Prezi learning media was carried out based on a problem found at SDN Jayabakti 03, namely the lack of teachers in utilizing learning media. As a result of the lack of use of learning media, it causes a decrease in students' interest in learning. The aim of the research is to develop learning media based on the Prezi digital application to increase students' interest in learning. The method for developing media uses Research and Development using the ADDIE design in media development. The results obtained from the validation of learning media obtained an average of 90% with the criteria "very valid". On the practicality of learning media, an average result of 95% was obtained by obtaining the "very practical" criterion. Regarding the effectiveness of the product in increasing interest in learning, the results were 89% by obtaining the "very high" criteria, so with this, Prezi digital application-based learning media can increase students' interest in learning.